2018
DOI: 10.1371/journal.pntd.0006423
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral responses of Rhodnius prolixus to volatile organic compounds released in vitro by bacteria isolated from human facial skin

Abstract: BackgroundPrevious studies have demonstrated the role of volatile organic compounds (VOCs) produced by skin microbiota in the attraction of mosquitoes to humans. Recently, behavioral experiments confirmed the importance of VOCs released by skin microbiota in the attraction of Rhodnius prolixus (Hemiptera: Triatominae), a vector of Chagas disease.Methods/FindingsIn this study, we screened for VOCs released in vitro by bacteria isolated from human facial skin that were able to elicit behavioral responses in R. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 34 publications
1
23
1
Order By: Relevance
“…The fact that R. prolixus is attracted by some VOCs released by some common bacteria of the human face skin, as Tabares and collaborators [39] showed, could be related to the close vertebrate-vector coevolutive history. However, the response of the bugs to the VOCs produced by C. koseri could make sense if the natural occurrence of the bacterium is considered: C. koseri is a gram-negative bacillus of the Enterobacteriaceae family, found in animal intestines, soils, water, sewage and contaminated food, and widely recognized for causing devastating meningitis in neonates and severe infections in immunosuppressed patients [44].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The fact that R. prolixus is attracted by some VOCs released by some common bacteria of the human face skin, as Tabares and collaborators [39] showed, could be related to the close vertebrate-vector coevolutive history. However, the response of the bugs to the VOCs produced by C. koseri could make sense if the natural occurrence of the bacterium is considered: C. koseri is a gram-negative bacillus of the Enterobacteriaceae family, found in animal intestines, soils, water, sewage and contaminated food, and widely recognized for causing devastating meningitis in neonates and severe infections in immunosuppressed patients [44].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies carried out in our laboratory have demonstrated the role that VOCs released by human facial skin microbiota play in the host-seeking behavior of R. prolixus [3941]. Tabares and collaborators [39] showed, in dual choice olfactometer experiments, that VOCs produced in vitro by some skin bacteria (at specific growth phases) had an attractive effect on R. prolixus . The authors also reported odor-source avoidance when some other bacteria VOCs were presented, such as those produced by Citrobacter koseri (Enterobacteriaceae).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations